ATRIBUTOS PARA QUALIDADE DO LUGAR EM COMUNIDADES TERAPÊUTICAS - Pimentel, Caroline Silva; Azevedo, Giselle Arteiro Nielsen (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This article is based on the relationships between people and the environment, specifically in entities that welcome people with disorders resulting from the use, abuse or dependence of psychoactive substances, also known as therapeutic community (TC). The objective of this work is to reflect on the importance of the environment built to promote the well-being of people, considering their needs and expectations, and to influence attributes that characterize the quality of the place in TC´s. The methodology consisted of a bibliographical and documentary review, and exploratory visits, with direct observations and field records. Visits confirmed that TC spaces are mostly not qualified for the activities developed as their users were not considered in the project. The results of the observations were related to the topics personal space, territoriality, and accessibility, offering directions for the conception of more human spaces, which could be appropriated.